Meningkatkan Daya Dukung Tiang Pondasi Minipile Persegi Pada Gedung Kantor Ngasem Kabupaten Kediri Menggunakan Metode Mayerhoff - Erwin Dwi Laksana; Edy Gardjito; Suwarno Suwarno; Faiz Muhammad Azhari; Imam Mustofa (Kadiri University, 2021)
The foundation is one part under the building that has a very important role. The choice of the type of foundation is something that needs to be considered. One type of foundation that is widely used is the minipile foundation. Minipile foundation itself is a type of foundation that is used if the load received from the superstructure is not too heavy and the hard soil type is at a depth of between 5-10m. The purpose of this study was to plan the bearing capacity of the minipile foundation pile in the PT. BPJE in Ngasem, Kediri Regency. The building is planned to be used as an office building. The planned sub-building includes foundation planning with a mini-square building with a cross-sectional dimension of 20x20. The calculations carried out include the calculation of the bearing capacity of the foundation using the Mayerhoff method, the calculation of the flexural factor and the calculation of reinforcement. The calculation results (sigma Vertical Ultimate) Vu = 114.78 tons. With bending factor tk = 286.95 kg /. The reinforcement in the pile cap for the x direction of tensile reinforcement = D16–170 and compression reinforcement = D16–250 while for tensile reinforcement in the y direction = D16 - 170 and compressive reinforcement = D10 - 250. Thus, the results of the planning can be used as a reference for the implementation of building construction. office of PT. BPJE in Ngasem, Kediri Regency.